The Pro-Oxidant Effect of Class A CpG ODNs on Human Neutrophils Includes Both Non-Specific Stimulation of ROS Production and Structurally Determined Induction of NO Synthesis - Ekaterina A. Golenkina; Svetlana I. Galkina; Galina M. Viryasova; Galina F. Sud’ina (Oxygen, 2023)
Synthetic CpG oligonucleotides are promising components of immunomodulatory drugs for the treatment and prophylaxis of infectious diseases, cancers, and allergies. Phosphorothioate modification stabilizes these compounds, contributing to the achievement of a clinical effect, but at the same time changes their immunomodulatory properties. We used the diffusible fluorescent dye dihydroethidium and the non-diffusible 6-carboxy-2′,7′dihydrochlorofluorescein diacetate and cytochrome c probes to demonstrate that it is the phosphorothioate backbones that determine the pronounced nonspecific pro-oxidant effect of CpG ODN on neutrophils. At the same time, as was shown using diaminofluorescein diacetate, the potentiation of nitric oxide synthesis in these leucocytes by CpG ODN class A strictly depends on the presence of CpG motifs and a palindromic “hairpin”. The results obtained will contribute to a more complete understanding of the physiological action of therapeutic agents based on synthetic CpG oligonucleotides.